The capability of class f contractor towards implementing IBS / Nurul Huda Abd Samad - Abd Samad, Nurul Huda (Faculty of Architecture, Planning and Surveying, 2010)
Industrialised Building System (IBS) can be defined as a technique of construction whereby components are manufactured in a controlled environment, either at site or off site, and transported, positioned and assembled into construction works. In our current industry, IBS acted as an effective and economical development In order to develop and adapt IBS, many parties involved, such Construction Industry Development Board, (CIDB), Industrialised Building System (IBS) Centre, Pusat Khidmat Kontraktor (PKK), Ministry of Works and local players. The parties involved are responsible to support and advice regarding the application of IBS in construction industry. The government has targeted more than 20 Bumiputra contractors especially class F, to capable in became vendors of Malaysia construction industry regarding Industrialised Building System (IBS) and distributor of construction materials. This research, will discusses about the capability of class F contractors based on knowledge towards implementation of IBS in industry. The study was conducted to identify the Industrialised Building System (IBS) that have been used in industry, then to identify the capability of class F based on their knowledge in IBS. Lastly, this research will identify the types of IBS that suitable for class F in industry. The set of questionnaires were distributed to the selected contractors randomly in area Selangor. An interview method was conducted in obtaining appropriate information regarding this research. All data collection were analyze in form of table or figure for easy understanding and readable.